Software sustainability requirements: A unified method for improving requirements process for software development - Dewi Saputri, Theresia Ratih; Lee, Seok Won (Proceedings of the IEEE International Conference on Requirements Engineering, 2021)
As one of the most important concepts in the software engineering process, requirements engineering plays an important task in sustainability engineering by understanding the nature of software system and their impacts on the entire dimension of sustainable development. Unfortunately, the process for incorporating sustainability concerns is not a trivial task. Sustainability is a concept with a high level of abstraction and is mostly treated as an afterthought. This work discusses a practical approach on how to capture requirements with sustainability concern related to software development. A stepwise guideline is presented to ease the requirements engineering process that can address sustainability issues. The proposed guideline combined well-known approaches such as the goal-scenario-based approach, analytical hierarchical approach, and feature modeling to capture sustainability requirements as an integrated framework. altogether, this tutorial shows a practical methodology in which the engineer can see which aspects or features that they need to improve to meet the required sustainability indicator and baseline.
Keywords: High level of abstraction; Nature of software; Requirement; Requirement engineering process; Requirements process; Software; Software engineering process; Software-systems; Sustainability issues; Unified method; Model; Requirements; Software; Sustainability